Influence of tibial shock feedback training on impact loading and running economy - Clansey, A. C.; Hanlon, M.; Wallace, E.; Nevill, A.; Lake, M. J. (Medicine & Science in Sports & Exercise, 2014)
4Purpose: The purpose of this study was to determine whether real-time feedback (RTF) training would reduce impact loading variables previously linked with tibial stress fracture risk and whether these adaptations would influence running economy.